Numerical simulation of mechanical flocculation in water treatment. Issue 4 (August 2021) - Zhan, Minshu; You, Minghao; Liu, Lingling; Zhang, Yilin; Yuan, Fang; Guo, Baoyu; Cheng, Guojian; Xu, Wei
Abstract: Flocculation plays a very important role in increasing the suspended solids removal and enhancing the phosphorous adsorption in wastewater treatment. In the current work, a combined model of computational fluid dynamics (CFD) and the population balance model (PBM) is proposed to simulate the flow characteristics and flocs behavior in a full scale flocculation. In order to relief computational efforts, the assumption of uniform particle size within the control volume is considered in the PBM model. The model considers the rotating flow in a mechanical flocculator, and the aggregation and breakage in the floc growth dynamics. Both the axial velocity and average floc size are validated with experimental measurements taken from literatures. The typical transportation phenomena of the flow velocity, local velocity gradient and floc size distribution are obtained. The inlet flow rate and initial floc particle size are investigated in the simulation. With the increasing of inlet flow rate, the floc particle size decreases, thus to cause the degradation of flocculation performance. The floc particle size linearly increases with the increasing of initial floc particle size, and the flocculation performance is correspondingly enhanced. These simulation results provide a profound understanding of the flocs growth mechanism, which is critical to the flocculation optimization. Graphical Abstract: ga1 Highlights: A CFD model combining with the PBM model is proposed to simulate the flocculation. The aggregation and breakage kernels are adopted to consider the flocs behavior. Both the axial velocity and average floc size are validated with experiments. Typical transportation phenomena in a full scale mechanical flocculator are obtained.